PERILAKU PALEOVOLKANO SEMADUM BERDASARKAN KARAKTER GEOKIMIA DAN PETROLOGI, KECAMATAN TUJUH BELAS, KABUPATEN BENGKAYANG, PROVINSI KALIMANTAN BARAT - Oky Sugarbo; Fuad Nur Hussein; Hill Gendoet Hartono; I Gde Sukadana (KURVATEK, 2021)
The phenomenon of the existence of the Semadum volcano fossil located in Pisak Village, Tujuhbelas District, Bengkayang Regency, West Kalimantan has a Pliocene-Plistocene age with a clear cone-shaped morphology. The purpose of this study was to determine the behavior of the Semadum volcano in relation to the character of the magma, the pattern and typical eruptions and distribution of its products. The methodology used is field activity and geochemical analysis using X-Ray Fluorescence (XRF), Micro X-ray fluorescence (µXRF) and petrography. The Semadum volcano is geochemically composed of basaltic products, basaltic trachy andesite and dacite with basal to dacitic magma character which has a calc-alkaline affinity related to the subduction process, making Semadum volcano has 5 periods of effusive and explosive eruption activity with the Strombolian- Vulcanian type eruption with an eruption strength ranging from VEI < 2 makes the distribution of its product not too wide, it only centers on the body of the volcano which is the construction phase. Keywords: Volcano, Geochemistry, Petrology, Bengkayang, West Kalimantan